Impact of ICT Integration on Students' Geometry Performance across Cognitive Domains - Ghimire, Shree Prasad (Curriculum Development Journal, 2025)
This study investigates the effects of Information and Communication Technology (ICT) integration on students' geometry performance across different cognitive levels. Using a pretest-posttest design, 157 students' geometry scores were analyzed across four cognitive domains: knowledge, understanding, application, and higher order thinking abilities. Analysis of Variance (ANOVA) was employed to determine significant differences between groups before and after ICT integration. Results revealed statistically significant improvements in overall geometry scores after ICT implementation (p < .001). Specifically, knowledge-level tasks showed the most dramatic improvement (p < .001), followed by higher-order thinking abilities (p = .007). Understanding-level performance showed statistically significant but smaller improvements (p = .011), while application-level tasks showed no statistically significant change (p = .332). These findings suggest that ICT integration has differential effects across cognitive domains, with particular benefits for foundational knowledge acquisition and higher-order thinking skills. Implications for educational practice and future research are discussed, highlighting the importance of targeted ICT implementation strategies aligned with specific cognitive learning objectives.